2009
DOI: 10.1159/000264735
|View full text |Cite
|
Sign up to set email alerts
|

Response of Chicken Ductus Arteriosus to Hypercarbic and Normocarbic Acidosis

Abstract: Background: Changes in pH can have profound effects on vascular tone and reactivity, but their influence on the ductus arteriosus (DA) remains unknown. Objective: To analyzethe effects of hypercarbic and normocarbic acidosis in the reactivity of the chicken DA. Methods: DA rings from 19-day chicken fetuses (total incubation time, 21 days) were mounted in a wire myograph for isometric tension recording. Results: In DA rings (pulmonary side) stimulated with O2, norepinephrine (NE), KCl, or U46619, cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 65 publications
3
5
0
Order By: Relevance
“…After an equilibration period of 30 min, the vessels were distended to a resting tension corresponding to a transmural pressure of 10 mmHg (15-day embryos) or 20 mmHg (19-day and 21-day embryos). These pressures correspond to the mean arterial blood pressure reported in chicken embryos at the corresponding age (6) and elicit the highest contractile response to KCl, as determined in previous experiments (33,46). After 30 min of incubation at basal tone, a control contraction was elicited by raising the K ϩ concentration of the buffer to 62.5 mM (in exchange for Na ϩ ).…”
Section: Methodssupporting
confidence: 85%
“…After an equilibration period of 30 min, the vessels were distended to a resting tension corresponding to a transmural pressure of 10 mmHg (15-day embryos) or 20 mmHg (19-day and 21-day embryos). These pressures correspond to the mean arterial blood pressure reported in chicken embryos at the corresponding age (6) and elicit the highest contractile response to KCl, as determined in previous experiments (33,46). After 30 min of incubation at basal tone, a control contraction was elicited by raising the K ϩ concentration of the buffer to 62.5 mM (in exchange for Na ϩ ).…”
Section: Methodssupporting
confidence: 85%
“…The expression of smooth muscle proteins and myosin heavy chain isoforms have been shown to be developmentally regulated and tissue dependent in mammals (Sakurai et al 1996; Slomp et al 1997). From the different chicken embryo vessels that our group have studied—carotid, femoral, pulmonary, chorioallantoic (CA) arteries, and ductus arteriosus (DA)—only the DA (Agren et al 2007; Flinsenberg et al 2010; Moonen et al 2010b) and the CA arteries (Lindgren et al 2010) showed an early “mature” contractile function at E15 comparable to the one observed in the MA (Fig. 5).…”
Section: Discussionmentioning
confidence: 89%
“…In the last few years, the chicken embryo has emerged as a suitable model for studying developmental vascular biology (Agren et al 2007, 2008, 2009; Moonen et al 2010b; Rouwet et al 2000; Ruijtenbeek et al 2002; Sutendra and Michelakis 2007; Villamor et al 2002; Zoer et al 2009, Zoer et al 2010a, b). In contrast to mammals, which depend on a continuous transference of nutrients from the maternal circulation to the developing fetus, all the nutrients required for the formation and growth of the chicken embryo are pre-packaged in the egg at the time of laying (Speake et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Its utility has been greatly extended during the last decade with the development of a variety of manipulation techniques [3,4,5]. Fundamental differences and advantages relative to mammals make the chicken embryo a complementary and valuable model for studies of lung function.…”
Section: Introductionmentioning
confidence: 99%